The Economics of Control Fraud - Prasch, Robert E. (Revista Economia Ensaios, 2014)
Fraud can take a variety of forms. For that reason we can expect that the individuals, or groups of individuals, engaged in it will undertake a variety of strategies depending upon the circumstances in which they find themselves. For this reason the "checks and balances" presumed to be adequate for detecting and suppressing fraud in any given firm or market may work passingly well in one instance but be less effective in another. Pursuant that notion, this paper will begin with a brief taxonomy of fraud before turning to a more in-depth discussion of the most pernicious form of fraud - Control Fraud.